2004
DOI: 10.1016/j.amjhyper.2004.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and blood pressureInteraction between the blood pressure-lowering effects of positive airway pressure therapy and antihypertensive drugs

Abstract: This study confirms an independent relationship between the severity of OSA and BP/HR. Absence of BP-lowering medication and BP values before treatment are independent predictors for the reduction of BP with Bi-/CPAP therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
2
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 26 publications
2
37
2
5
Order By: Relevance
“…Although previous analyses have addressed some aspects of the effects of PAP on measures of cardiac and vascular function,16, 42 to the best of our knowledge, our results are the first to identify early changes in vascular stiffness, endothelial function, and cardiac hemodynamics in young individuals with moderate‐to‐severe OSA and identify their changes in response to PAP treatment and its withdrawal. A major strength of our study is the robustness and consistency of our data, as well as the use of objective PAP compliance information.…”
Section: Discussionmentioning
confidence: 91%
“…Although previous analyses have addressed some aspects of the effects of PAP on measures of cardiac and vascular function,16, 42 to the best of our knowledge, our results are the first to identify early changes in vascular stiffness, endothelial function, and cardiac hemodynamics in young individuals with moderate‐to‐severe OSA and identify their changes in response to PAP treatment and its withdrawal. A major strength of our study is the robustness and consistency of our data, as well as the use of objective PAP compliance information.…”
Section: Discussionmentioning
confidence: 91%
“…There have been four reports illustrating a long-term (more than 6 months) effect of nasal CPAP on OSAS parameters [7,[30][31][32]. As noted above, the use of CPAP in this patient was on 85.7% of the days, and the mean measured use time was 5 hr 51 min.…”
Section: Discussionmentioning
confidence: 97%
“…Several investigators have reported a reduction of plasma and/or urinary NE and systemic blood pressure as early as the first night on CPAP [28,29]. Recent controlled studies demonstrated that nasal CPAP therapy for 4-9 weeks reduced blood pressure by 1-10 mmHg [4][5][6][7], in that the degree of blood pressure reduction appeared to be dependent on the severity of established hypertension. In agreement with this notion, Heitmann et al found that blood pressure and plasma NE levels were reduced in hypertensive, but not normotensive, OSAS patients after a minimum of 4 weeks of home use of nasal CPAP therapy [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these studies vary somewhat in their designs, all 3 allowed the subset of hypertensive patients in their studies to remain on antihypertensive medications. This makes their divergent results difficult to interpret, because use of antihypertensive medications has been reported by some authors as a positive predictor 50 but by others a negative predictor 60 of the potential blood pressure-lowering effects of CPAP therapy.…”
mentioning
confidence: 80%